Giving monoclonal antibodies to healthy volunteers in phase 1 trials: is it safe?. (23rd July 2013) - Tranter, Elizabeth; Peters, Gary; Boyce, Malcolm; Warrington, Steve
<x xml:space="preserve">Abstract</x> Many monoclonal antibodies (MAbs) have been studied in healthy volunteers in phase 1, but few data have been published on the safety of that practice. We aimed to review the available data, and thereby to estimate the risks of participation in phase 1 trials of MAbs. We searched PubMed, the ClinicalTrials.gov database and Google, using the search terms 'monoclonal antibody', 'phase 1' and 'healthy volunteers'. We identified 70 completed trials of MAbs in healthy volunteers, but the published data were too sparse to allow confident assessment of the risks of MAbs in healthy volunteers. Our best estimate of risk of a life‐threatening adverse event was between 1 : 425 and 1 : 1700 volunteer‐trials, but all such events occurred in a single trial (of TGN1412). In a phase 1 trial of a small molecule, the risk of death or a life‐threatening adverse event appears to be 1 : 100 000–1 000 000 volunteer‐trials, which is similar to the risk of many ordinary daily activities. Most people would consider that level of risk to be 'minimal' or 'negligible' and, therefore, acceptable. On that basis, the safety record of MAbs in healthy volunteers has been ruined by the TGN1412 disaster. However, that experience is unlikely to be repeated, because of improvements in governance and practice of phase 1 trials. If the experience of TGN1412 is disregarded, it seems reasonable to continue using healthy volunteers in phase 1 trials of MAbs, provided that there are scientific and medical reasons to conclude that the risk is truly minimal.